Arctic Voices. Resistance at the Tipping Point [Reseña de Libro] - Hennig, Reinhard (Universidad de Alcalá, 2013)
Reseña de Libro: Subhankar Banerjee, ed. Arctic Voices. Resistance at the Tipping Point. New York: Seven Stories Press, 2012, 550 pp.